Overexpression of TIFY genes promotes plant growth in rice through jasmonate signaling. Issue 5 (4th May 2017) - Hakata, Makoto; Muramatsu, Masayuki; Nakamura, Hidemitsu; Hara, Naho; Kishimoto, Miho; Iida-Okada, Keiko; Kajikawa, Mariko; Imai-Toki, Naoko; Toki, Seiichi; Nagamura, Yoshiaki; Yamakawa, Hiromoto; Ichikawa, Hiroaki
Abstract: Because environmental stress can reduce crop growth and yield, the identification of genes that enhance agronomic traits is increasingly important. Previous screening of full-length cDNA overexpressing (FOX) rice lines revealed that OsTIFY11b, one of 20 TIFY proteins in rice, affects plant size, grain weight, and grain size. Therefore, we analyzed the effect of OsTIFY11b and nine other TIFY genes on the growth and yield of corresponding TIFY-FOX lines. Regardless of temperature, grain weight and culm length were enhanced in lines overexpressing TIFY11 subfamily genes, except OsTIFY11e. The TIFY-FOX plants exhibited increased floret number and reduced days to flowering, as well as reduced spikelet fertility, and OsTIFY10b, in particular, enhanced grain yield by minimizing decreases in fertility. We suggest that the enhanced growth of TIFY-transgenic rice is related to regulation of the jasmonate signaling pathway, as in Arabidopsis. Moreover, we discuss the potential application of TIFY overexpression for improving crop yield. Abstract : :